Noggin Overexpression Impairs the Development of Muscles, Tendons, and Aponeurosis in Soft Palates by Disrupting BMP-Smad and Shh-Gli1 Signaling - Deng, Jiamin; Wang, Shangqi; Li, Nan; Chen, Xiaoyan; Wang, Biying; Liu, Han; Zhu, Lei; Cong, Wei; Xiao, Jing; Liu, Chao (Frontiers in Cell and Developmental Biology, 2021)
The roles of BMP signaling in palatogenesis were well documented in the developing hard palate, however, little is known about how BMP signaling regulates the development of soft palate. In this study, we over-expressed Noggin transgene via Osr2-creKI allele to suppress BMP signaling in the developing soft palate. We found that BMP-Smad signaling was detected in the palatal muscles and surrounding mesenchyme. When BMP-Smad signaling was suppressed by the over-expressed Noggin, the soft palatal shelves were reduced in size with the hypoplastic muscles and the extroversive HPP. The down-regulated cell proliferation and survival in the Osr2-creKI;pMes-Noggin soft palates were suggested to result from the repressed Shh transcription and Gli1 activity, implicating that the BMP-Shh-Gli1 network played the similar role in soft palate development as in hard palate. The down-regulated Sox9, TnC and Col1 expression in Osr2-creKI;pMes-Noggin soft palate indicated that the impaired differentiation of the apoeurosis and tendons, which was suggested to result in the hypoplasia of palatal muscles. Intriguingly, in the Myf5-creKI;pMes-Noggin and the Myf5-creKI;Rosa26R-DTA soft palates, the hypoplastic or abrogated muscles affected the fusion of soft palate little. Although the Scx, Tnc and Co1 transcription was significantly repressed in the tenogenic mesenchyme of the Myf5-creKI;pMes-Noggin soft palate, the Sox9 expression, and the Tnc and Col1 transcription in apoeurosis mesenchyme were almost unaffected. It implicated that the fusion of soft palate was controlled by the mesenchymal clues at the TVP and LVP levels, but by the myogenic components at the PLP level.